Positive pole piece and secondary battery
By regulating the heat release characteristic parameters and tortuosity of the positive electrode of lithium-ion secondary batteries, the problems of safety and low lithium ion transmission efficiency of ternary materials in lithium-ion secondary batteries are solved, and higher thermal stability and kinetic performance are achieved.
Patent Information
- Application Number
- CN202511174162.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-21
- Publication Date
- 2025-09-23
- Estimated Expiration
- 2045-08-21
AI Technical Summary
The safety improvement of ternary positive electrode materials in existing lithium-ion secondary batteries and the low lithium ion transmission efficiency, especially the decline in kinetic performance under special environments, cannot take into account the overall indicator level.
By regulating the exothermic characteristic parameters and tortuosity of the ternary materials in the positive electrode, their safety, stability and lithium ion transmission efficiency can be synergistically improved. The specific methods include controlling the ratio of the total peak area of the exothermic characteristic peak to the highest peak temperature (a/b=0.5~8) and the tortuosity (b=1~5), and using nickel cobalt manganese oxide particles as active materials in the electrode.
It improves the thermal stability and kinetic performance of secondary batteries, ensures high lithium ion transmission efficiency, reduces internal heat generation, and improves overall safety and uniformity of the charging and discharging process.
Smart Images

Figure CN120690808A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a positive electrode sheet and a secondary battery. Background Art
[0002] Ternary cathode materials in lithium-ion secondary batteries offer high energy density, but safety, particularly stability under specific circumstances, remains a key area of improvement. Furthermore, some safety improvements for ternary cathode materials can reduce the material's inherent lithium-ion transport efficiency, discharge capacity, and kinetic performance, failing to maintain a consistent overall product performance. Summary of the Invention
[0003] The purpose of this application is to overcome the shortcomings of the existing technology and provide a positive electrode plate. By coordinating the heat release characteristic parameters of the ternary material in the positive electrode plate and the tortuosity of the plate, it is possible to effectively improve the overall safety and stability of the positive electrode plate, while improving the efficiency of the ternary material in the plate during the lithium ion transmission process, thereby ensuring better kinetic performance.
[0004] To achieve the above-mentioned object, in a first aspect of the present application, the present application provides a positive electrode plate, the positive electrode plate comprising a positive electrode material layer, the positive electrode material layer comprising a positive electrode active material, the positive electrode active material comprising lithium nickel cobalt manganese oxide particles; The positive electrode sheet satisfies: a / b=0.5~8; Said a=S / T, where SJ / g is the total peak area of the exothermic characteristic peak of the positive electrode between 190°C and 290°C during the DSC (differential scanning calorimetry) test, and T°C is the temperature corresponding to the highest peak of the test exothermic characteristic peak; The b is the tortuosity of the positive electrode sheet.
[0005] The beneficial effects of this application are: The present application provides a positive electrode plate, which can effectively improve the overall safety and stability of the positive electrode plate by coordinating the heat release characteristic parameters of the ternary material in the positive electrode plate and the tortuosity of the plate, while improving the efficiency of the ternary material in the plate during the lithium ion transmission process, thereby ensuring better kinetic performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0006] Figure 1 This is a schematic diagram of the characteristic exothermic peaks of the positive electrode sheet described in Example 5 of the present application during DSC testing. DETAILED DESCRIPTION
[0007] To make the purpose, technical solutions, and advantages of the embodiments of this application more clear, the technical solutions in the embodiments of this application will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of this application, not all of them. Based on the embodiments of this application, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of this application.
[0008] In this application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0009] In this application, when referring to numerical ranges, unless otherwise specified, the numerical ranges are considered continuous and include the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe a feature or characteristic, the ranges can be combined. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges subsumed therein.
[0010] The present application is further described below with specific examples: A positive electrode plate, comprising a positive electrode material layer, the positive electrode material layer comprising a positive electrode active material, and the positive electrode active material comprising lithium nickel cobalt manganese oxide particles; The positive electrode sheet satisfies: a / b=0.5~8; Said a=S / T, wherein SJ / g is the total peak area of the exothermic characteristic peak of the positive electrode sheet between 190 and 290°C during the DSC test, and T°C is the temperature corresponding to the highest peak of the test exothermic characteristic peak; The b is the tortuosity of the positive electrode sheet.
[0011] When used as a cathode material, the ternary material nickel cobalt manganese oxide particles have a high energy density, but there is still much room for improvement in terms of safety. In particular, after being prepared into a secondary battery, when conducting an ARC (adiabatic calorimeter) thermal runaway test, the measured critical thermal runaway temperature of the secondary battery is relatively low, which limits its use in some special working environments. To this end, in the present application, after the positive electrode sheet uses nickel cobalt manganese oxide particles as the positive electrode active material, the overall heat release range characteristics of the positive electrode sheet are adjusted, that is, the ratio of the total peak area of the heat release characteristic peak to the temperature corresponding to the highest peak of the characteristic peak, so as to improve the thermal stability of the positive electrode sheet after being prepared into a secondary battery, and the critical temperature of thermal runaway can be significantly improved; on the other hand, when adjusting the thermodynamic stability of the positive electrode sheet, its kinetic performance during the charging and discharging process also needs to be considered. Therefore, it is necessary to coordinately adjust the tortuosity of the positive electrode sheet, so that the nickel cobalt manganese oxide particles on the positive electrode sheet can achieve a better electrochemical environment distribution, high electrochemical reaction uniformity, and lithium ion transmission efficiency maintained at a high level. When applied to secondary batteries, it can achieve excellent effects in both safety and kinetic performance.
[0012] In some embodiments, a / b=0.5~8.
[0013] Further preferably, a / b is in the range of one or any two of 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8.
[0014] More preferably, a / b=3~6.
[0015] The exothermic characteristic parameter S / T of the positive electrode sheet represents the interaction between the positive electrode material in the positive electrode sheet and the electrolyte when used in a secondary battery. During this process, as the internal temperature of the battery increases, the electrolyte decomposes, the nickel cobalt manganese oxide particles undergo phase change and decomposition, and the heat generation inside the battery increases. By regulating the ratio of the exothermic peak area and the exothermic peak temperature, the internal heat generation of the battery when the positive electrode sheet is used in the battery can be effectively regulated, so that the battery has a higher critical thermal runaway temperature and ensures that the battery has sufficient thermal stability and safety. At the same time, the regulation of thermal stability needs to take into account the kinetic performance of the nickel cobalt manganese oxide particles in the positive electrode sheet during charging and discharging. Therefore, the tortuosity of the electrode sheet needs to be regulated simultaneously. When the a / b of the positive electrode sheet is preferably within the above range, not only is the overall thermal stability of the positive electrode sheet higher, but also after the positive electrode sheet is assembled into a secondary battery, the electrolyte infiltration of the electrode sheet is higher, the structural stability is higher, the stress dispersion uniformity during the charging and discharging process is high, and rapid lithium ion insertion and extraction and good electrochemical stability are maintained, the kinetic performance is better, and the DCR is lower.
[0016] In some embodiments, a=1.5~12.
[0017] Further preferably, a is a range value of one or any two of 1.5, 2, 2.4, 2.45, 2.5, 3, 3.5, 3.75, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 7.8, 8, 9, 10, 11, 12.
[0018] More preferably, a=3~9.
[0019] In the present application, a=S / T, wherein S represents the exothermic peak area, reflecting the intensity of the exothermic release, T represents the temperature corresponding to the highest peak of the exothermic peak, and S / T represents the exothermic intensity ratio of the positive electrode plate. When the characteristic peak area is small and the peak temperature is large, the thermal stability of the positive electrode plate is better, but at this time the passivation degree of the surface of the positive electrode plate will also increase, which will reduce the lithium ion transmission rate and the kinetic performance. When the ratio of the characteristic peak area to the peak temperature is preferably within the above range, the positive electrode plate can achieve better thermodynamic stability. At this time, the interaction reaction between the interface of the positive electrode material layer and the electrolyte becomes less, the internal heat generation is reduced, and the thermal stability of the secondary battery is improved, so the safety is better. At the same time, it can also take into account the good kinetic performance of the positive electrode plate during charging and discharging, and the DCR is low.
[0020] In some embodiments, the S=400~2600 J / g.
[0021] Further preferably, S=one or any two of 400 J / g, 700 J / g, 800 J / g, 900 J / g, 1000 J / g, 1200 J / g, 1400 J / g, 1500 J / g, 1800 J / g, 2000 J / g, 2200 J / g, 2400 J / g, and 2600 J / g.
[0022] More preferably, the S=900~2200 J / g.
[0023] When the total peak area of the characteristic exothermic peak of the positive electrode plate between 190 and 290°C during the DSC test is preferably within the above range, it can not only ensure that the internal heat generation is low and the thermal stability is good when used in a secondary battery, but also ensure that the positive electrode plate will not be excessively passivated, the lithium ion transfer kinetics performance is at a high level, and the overall performance is better.
[0024] In some embodiments, the temperature is T=190-290°C.
[0025] More preferably, T is in the range of one or any two of 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, and 290°C.
[0026] More preferably, the temperature T is 220-260°C.
[0027] Similar to S, when the peak temperature of the exothermic characteristic peak of the positive electrode during the DSC test is preferably within the above range, it can not only ensure its thermal stability when applied to secondary batteries, but also take into account better kinetic performance, high lithium ion transmission efficiency and lower DCR.
[0028] It should be noted that in the technical solution of the present application, the a can be tested by, but not limited to, the following method: the secondary battery is discharged to 0% SOC at 0.33C, and then charged to 4.25V at 0.33C, with a cut-off current of less than 0.05C, the secondary battery is disassembled in a glove box, the obtained positive electrode sheet is soaked in DMC for 2 hours and then dried, the positive electrode material layer on the current collector is scraped and placed in the test chamber of a DSC (differential scanning calorimeter) test instrument (model DSC214), and then the electrolyte is added. , wherein the amount of electrolyte used matches the amount of powder added, 1 mg of powder corresponds to 1 μL of electrolyte, EC (ethylene carbonate), EMC (ethyl methyl carbonate), and DEC (diethyl carbonate) are mixed in a mass ratio of 1:1:1 as a solvent, and then lithium hexafluorophosphate is added to the mixture to a concentration of 1 mol / L; the protective atmosphere is set to nitrogen, and the temperature is increased from 25°C to 400°C at a heating rate of 5 K / min to obtain a test spectrum, and the spectrum is analyzed and integrated to obtain the S and T, and a is obtained by calculation.
[0029] In some embodiments, b=1~5.
[0030] Further preferably, b is a range value of one or any two of 1, 1.2, 1.5, 1.8, 2, 2.2, 2.5, 2.8, 3, 3.2, 3.5, 3.8, 4, 4.2, 4.5, 4.8, 5.
[0031] More preferably, b=1.5~3.5.
[0032] The tortuosity of the positive electrode sheet affects its wettability in the secondary battery, the electrochemical environment of the nickel cobalt manganese oxide particles during the charging and discharging process, and the transmission network efficiency during lithium ion transmission. When the tortuosity of the positive electrode sheet is preferably within the above range, it can not only effectively avoid the negative impact of the anisotropy of the nickel cobalt manganese oxide particles, but also have better structural stability. At the same time, the charge and discharge activity of the particles on the surface and bottom layers are both high, the lithium ion transmission efficiency is higher, the initial DCR is low, and the kinetic performance is better.
[0033] In some embodiments, the lithium nickel cobalt manganate particles further include a shell comprising at least one of Al2O3, ZrO2, LiAlO2, Li3PO4, LATP (lithium aluminum titanium phosphate), LLZO (lithium lanthanum zirconium oxide), and LLTO (lithium lanthanum titanate).
[0034] In the present application, relatively inert metal oxides such as aluminum oxide and solid electrolytes such as LATP are used to coat lithium nickel cobalt manganese oxide particles, which can effectively improve the thermal stability and chemical stability of lithium nickel cobalt manganese oxide. After synchronously regulating the heat release characteristics of the particle material and the tortuosity characteristics of the electrode itself, the secondary battery corresponding to the electrode can achieve effective thermal stability and dynamic performance.
[0035] More preferably, the average thickness of the shell is 5-500 nm.
[0036] It should be noted that, in the present application, the average thickness of the shell can be confirmed by, but not limited to, the following methods: soaking the positive electrode plate in DMC for 2 hours and then drying it, scraping the positive electrode material layer, and sintering the obtained powder at 450°C for 6 hours in an air atmosphere. The cross-section of the test sample is polished using an argon ion beam, and four test samples are grouped together. The polished samples are prepared by EPMA (electron probe X-ray microanalysis) using anhydrous ethanol as a dispersion liquid. The prepared samples are placed on a sample stage and photographed. The shooting position is the edge of the shell of the lithium nickel cobalt manganese oxide particles and at least four positions are selected. The coating thickness is calculated according to the ruler, and the final result is averaged based on 16 groups of data.
[0037] In some embodiments, the particle size Dv50 of the positive electrode active material is 1.5-6 μm.
[0038] More preferably, the particle size Dv50 of the positive electrode active material is in the range of one or any two of 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, and 6 μm.
[0039] In some embodiments, the positive electrode active material has a SPAN value of 1 to 1.5; the SPAN value = (particle size Dv90 of the positive electrode active material / particle size Dv10 of the positive electrode active material) / particle size Dv50 of the positive electrode active material.
[0040] It should be noted that the particle size Dv50 and SPAN value of the positive electrode active material in the positive electrode sheet described in this application can be confirmed by, but not limited to, the following methods: The positive electrode sheet was soaked in DMC for 2 hours and then dried. The positive electrode material layer was scraped and the resulting powder was sintered at 450°C for 6 hours in an air atmosphere. Subsequently, a laser particle size distribution analyzer (Mastersizer 3000) was used to measure the particle size distribution according to the particle size distribution laser diffraction method (refer to GB / T19077-2016 for specific steps). The particle size at which the cumulative volume distribution reaches 50% was Dv50; the particle size at which the cumulative volume distribution reaches 10% was Dv10; and the particle size at which the cumulative volume distribution reaches 90% was Dv90.
[0041] In some embodiments, the specific surface area of the positive electrode active material is 0.4 to 1.2 m 2 / g.
[0042] Further preferably, the specific surface area of the positive electrode active material is 0.4 m 2 / g, 0.6 m 2 / g, 0.8 m 2 / g、1m 2 / g, 1.1 m 2 / g, 1.2 m 2 / g or both.
[0043] It should be noted that the specific surface area of the positive electrode active material in the positive electrode sheet described in the present application can be determined by, but not limited to, the following methods: The positive electrode sheet was soaked in DMC for 2 hours and then dried. The positive electrode material layer was scraped and the obtained powder was sintered at 450°C for 6 hours in an air atmosphere. The BET specific surface area was then tested using the nitrogen adsorption-desorption method.
[0044] In some embodiments, the porosity of the positive electrode sheet is 13-35%.
[0045] Further preferably, the porosity of the positive electrode sheet is in the range of one or any two of 13%, 15%, 18%, 20%, 22%, 25%, 28%, 30%, 32%, and 35%.
[0046] It should be noted that the porosity of the positive electrode sheet described in this application can be confirmed by, but not limited to, the following methods: The positive electrode sheet was cut into discs with a diameter of D = 12 mm. The thickness of the electrode sheet and the current collector were measured with a thickness gauge, and recorded as h1 and h2 respectively ... 2 (h1-h2) Calculate the volume V1 of the positive electrode active material layer, then weigh the mass of the electrode and record it as m1. Then place the electrode in a sealed container and completely immerse it in hexadecane for 1 hour (the volume of hexadecane in the sealed container is not required, but the required amount must be able to ensure that the electrode is completely immersed in it). Take it out and adsorb it on filter paper to dry it to constant weight (generally 1 hour). Weigh and record it as m2. The porosity of the positive electrode is obtained by the formula porosity% = (m2-m1 / ρ) / V1×100%, where ρ is the density of hexadecane, 0.7734g / cm 3 .
[0047] In some embodiments, the compacted density of the positive electrode sheet is 3.25-3.65 g / cm 3 .
[0048] It should be noted that the compaction density of the positive electrode sheet described in this application can be confirmed by, but not limited to, the following methods: Use a punching machine to punch the pre-treated positive electrode sheet into discs of fixed area. The area is recorded as S0 in mm. 2 ; In order to ensure the accuracy of the test, select a piece from the middle and flat position of the electrode, and take three or more discs as parallel samples, and then use an electronic balance to weigh the mass of each disc respectively. The mass of each disc is recorded as M1, unit, g, and the thickness of the active material layer in the three discs is tested with a micrometer (the thickness after removing the current collector), recorded as H, unit mm; take the average value, and finally add an appropriate amount of deionized water to each of the three discs, gently wipe off the coating on the disc with dust-free paper to expose the copper foil, and let it stand (dry) at room temperature for 10 minutes. After the copper foil is dry, weigh the mass of the three copper foils respectively, record it as M0, take the average value, and calculate the coating compaction density A according to the following formula: A=(M1-M0) / (H*S0).
[0049] In some embodiments, the structural formula of the lithium nickel cobalt manganese oxide is LiNi a Co b Mn c O2, where a is greater than 0 and less than 1; b is greater than 0 and less than 1; c is greater than 0 and less than 1; a+b+c=1.
[0050] In some embodiments, the lithium nickel cobalt manganese oxide particles further contain a doping element, wherein the doping element includes at least one of Al, Mg, and Ti. In some embodiments, the lithium nickel cobalt manganese oxide particles can be commercially available products or can be obtained by a homemade method. Specifically, the lithium nickel cobalt manganese oxide particles can be obtained by the following preparation method: A nickel source, a cobalt source and a manganese source are mixed in a solvent, a precipitant is added for precipitation reaction, and the mixture is allowed to stand. After filtering, washing and drying, the obtained mixed precursor is mixed with a lithium source and calcined once. The obtained material is then crushed and sieved, mixed with a coating material, calcined twice, and sieved to obtain the nickel cobalt manganese oxide lithium particles.
[0051] In some embodiments, the nickel source includes at least one of nickel sulfate, nickel nitrate, nickel chloride, nickel oxalate, and nickel acetate; In some embodiments, the cobalt source used includes at least one of cobalt sulfate, cobalt nitrate, cobalt chloride, cobalt oxalate, and cobalt acetate; In some embodiments, the manganese source includes at least one of manganese sulfate, manganese nitrate, manganese chloride, manganese oxalate, and manganese acetate; In some embodiments, the lithium source includes at least one of lithium hydroxide, lithium carbonate, lithium nitrate, lithium oxalate, lithium dihydrogen phosphate, lithium citrate, and lithium acetate; In some embodiments, the precipitant includes at least one of sodium hydroxide, sodium carbonate, oxalic acid, and ammonia water.
[0052] In some embodiments, the solvent comprises water.
[0053] In some embodiments, the precipitation reaction time is 0.5 to 1.5 hours.
[0054] In some embodiments, the heating rate during the primary calcination is 1-10° C. / min, the calcination temperature is 800-920° C., and the calcination time is 10-15 h.
[0055] In some embodiments, the coating material includes at least one of Al2O3, ZrO2, LiAlO2, Li3PO4, LATP (lithium aluminum titanium phosphate), LLZO (lithium lanthanum zirconium oxide), and LLTO (lithium lanthanum titanate).
[0056] In some embodiments, the heating rate during the secondary calcination is 1-10° C. / min, the calcination temperature is 450-470° C., and the time is 4-5 h.
[0057] In some embodiments, the mixing can be achieved by ball milling, and the ball milling time is 1.5 h to 2.5 h, and the rotation speed is 400 to 500 r / min.
[0058] In some embodiments, the mass percentage of manganese ions in the surface layer of the lithium nickel manganese cobalt oxide particles is greater than the mass percentage of manganese ions in the inner layer.
[0059] By setting a gradient manganese ion concentration, lithium nickel cobalt manganese oxide particles can have better thermal stability and safety performance when used as positive electrode active materials.
[0060] In some embodiments, during the secondary calcination, the obtained material is further mixed with manganese dioxide.
[0061] In some embodiments, the positive electrode material layer in the positive electrode sheet includes a positive electrode material, a binder, and a conductive agent. The positive electrode material includes lithium nickel cobalt manganese oxide particles, and the mass percentage of the positive electrode material in the positive electrode material layer is 92-99%.
[0062] In some embodiments, the binder is used to improve the adhesion between the positive electrode active material particles and the adhesion between the positive electrode active material and the positive electrode current collector. Any binder can be used without particular limitation, as long as it has suitable binding properties and does not significantly cause adverse chemical changes in the battery. For example, the binder includes a fluorinated polyolefin binder, which includes but is not limited to polyvinylidene fluoride (PVDF), vinylidene fluoride copolymers, or modified derivatives thereof (e.g., modified with carboxylic acid, acrylic acid, acrylonitrile, etc.).
[0063] Specifically, the binder is selected from polytetrafluoroethylene or polyvinylidene fluoride.
[0064] In some embodiments, the mass percentage of the binder in the positive electrode material layer is 1% to 4.0%, such as 1%, 1.2%, 1.5%, 1.8%, 2.0%, 2.2%, 2.5%, 2.7%, 3.0%, 3.2%, 3.5%, 3.8%, 4.0% or an interval formed by any two of the above values.
[0065] In some embodiments, the conductive agent is used to provide electrical conductivity. Any conductive agent can be used without particular limitation, as long as it has suitable electronic conductivity and does not significantly cause adverse chemical changes in the battery. Exemplary conductive agents in the positive electrode active material layer include, but are not limited to, at least one of carbon nanotubes, carbon black, graphite, carbon fibers, activated carbon, mesoporous carbon, and fullerenes, wherein carbon fibers include carbon nanofibers, and carbon black includes SP (Super P, the same below), acetylene black, and Ketjen black.
[0066] In some embodiments, the mass percentage of the conductive agent in the positive electrode material layer is 1.0% to 4.0%, such as 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.5%, 3%, 3.5%, 4% or an interval formed by any two of the above values.
[0067] In some embodiments, the positive electrode plate can be prepared by, but not limited to, the following method: The positive electrode active material, the conductive agent and the binder are mixed in a solvent and then stirred to prepare a slurry. The slurry is coated on a current collector in a single layer or double layer, dried, rolled and cut to obtain the positive electrode sheet.
[0068] In some embodiments, the solvent includes N-methylpyrrolidone (NMP).
[0069] In some embodiments, the tortuosity of the positive electrode plate of the present application can be controlled by, but is not limited to, the particle size of the positive electrode material selected during the preparation of the positive electrode plate, the compaction density of the positive electrode plate (that is, regulating the pressure of rolling the positive electrode plate), and punching the plate to set concave holes (regulating the depth of the punching, etc.). Those skilled in the art may also use other means to control the tortuosity, which is not specifically limited here.
[0070] In some embodiments, the positive electrode material layer of the positive electrode plate is further provided with a plurality of concave holes, the ratio of the depth of the concave holes to the thickness of the positive electrode material layer is (0.2-0.96):1, the pore diameter of the concave holes is 2-40 μm, and the pore density of the concave holes is 6-500 pt / m 2 .
[0071] Furthermore, the concave holes are arranged on a side of the active material layer away from the current collector.
[0072] Another object of the present application is to provide a secondary battery comprising the positive electrode sheet described in the present application.
[0073] In some embodiments, the lithium-ion battery further includes a negative electrode plate and an electrolyte.
[0074] In some embodiments, the electrolyte includes an additive, a solvent, and a lithium salt.
[0075] In some embodiments, the solvent includes at least one of a carbonate solvent, a carboxylate solvent, an ether solvent, a sulfone solvent, a nitrile solvent, and a phosphate solvent.
[0076] Illustratively, the carbonate solvent includes but is not limited to at least one of propylene carbonate (PC), ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC); the carboxylate solvent includes but is not limited to at least one of ethyl acetate, methyl formate, and 1,4-butyrolactone; the ether solvent includes at least one of dimethyltetrahydrofuran, tetrahydrofuran, and 1,2-dimethoxyethane; the sulfone solvent includes at least one of methyl sulfone and dimethyl sulfoxide; the nitrile solvent includes at least one of propionitrile, butyronitrile, 1-(2-cyanoethyl)pyrrole, and 1,3,6-hexanetrinitrile; and the phosphate solvent includes at least one of trimethyl triphosphate and triethyl phosphate.
[0077] More preferably, the carbonate solvent accounts for 70-100% by mass based on the total solvent mass in the electrolyte.
[0078] When the tortuosity and thermal stability parameters of the positive electrode sheet meet the specified requirements, further adaptation using the above-mentioned preferred electrolyte solvent formula can greatly increase the rate of lithium ion transmission in the secondary battery, thereby improving the kinetic performance of the secondary battery.
[0079] In some embodiments, the lithium salt includes at least one of lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium perchlorate, lithium tetrafluoroborate, lithium bisoxalatoborate, lithium difluorooxalatoborate, lithium trifluoromethanesulfonate, lithium bisfluoromethanesulfonyl imide, lithium bistrifluoromethanesulfonyl imide, lithium difluorobisoxalatophosphate, lithium tetrafluorooxalatophosphate, and the like.
[0080] In some embodiments, the additive includes, but is not limited to, vinylene carbonate.
[0081] Further preferably, the additive includes at least one of 2,2,2-trifluoroethyl methyl carbonate, pentafluoroethoxy cyclotriphosphazene, and vinyl sulfate.
[0082] When using a positive electrode plate of a nickel cobalt lithium manganese oxide system, selecting an electrolyte containing the above-mentioned additive types can effectively take into account both the safety performance and fast charging performance of the secondary battery.
[0083] In some embodiments, the negative electrode plate includes a negative electrode material layer, the negative electrode material layer includes a negative electrode material, and the negative electrode material includes at least one of natural graphite, artificial graphite, mesophase carbon microbeads, hard carbon, soft carbon, elemental silicon, silicon oxide, silicon-carbon composite material, and lithium titanate.
[0084] In some embodiments, the negative electrode material includes graphite, and the positive electrode plate satisfies: b=1.8~5.
[0085] Further preferably, the graphite includes at least one of artificial graphite and natural graphite.
[0086] When lithium nickel cobalt manganese oxide particles are selected as the active material of the positive electrode and the negative electrode material in the negative electrode plate contains graphite, the overall dynamic performance is better than other systems due to the good strength and conductivity of graphite itself. The tortuosity of the positive electrode plate can be preferably within the above range to make the lithium ion conduction efficiency higher. In some embodiments, the negative electrode material includes a silicon-based material, and the positive electrode plate satisfies: b=1~4.5.
[0087] Further preferably, the silicon-based material includes at least one of elemental silicon, silicon monoxide, silicon carbide, and a silicon-carbon composite material.
[0088] The kinetic properties of silicon-based materials are poorer than those of carbon-based materials. In order to achieve better lithium ion conduction efficiency, when the negative electrode material contains silicon-based materials, it is further preferred that the tortuosity of the positive electrode plate is within the above-mentioned range, so as to improve the lithium ion conduction efficiency of the overall secondary battery through the high kinetic properties of the positive electrode plate.
[0089] The negative electrode material layer may further include a conductive agent and / or a binder.
[0090] The conductive agent in the negative electrode active material layer is used to provide electrical conductivity. Any conductive agent can be used without particular limitation, as long as it has suitable electronic conductivity and does not significantly cause adverse chemical changes in the battery. Exemplary conductive agents include, but are not limited to, at least one of carbon nanotubes, carbon black, graphite, carbon fibers, activated carbon, mesoporous carbon, and fullerenes. Examples of carbon fibers include carbon nanofibers; and examples of carbon black include SP, acetylene black, and Ketjen black.
[0091] In some embodiments, the mass percentage of the conductive agent in the negative electrode material layer is 0.4% to 2%, such as 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2% or an interval formed by any two of the above values.
[0092] The binder in the negative electrode active layer is used to improve the adhesion between the negative electrode active material particles and the adhesion between the negative electrode active material and the negative electrode current collector. Any binder can be used without particular limitation, as long as it has suitable binding properties and does not significantly cause adverse chemical changes in the battery. Exemplary binders include, but are not limited to, at least one of carboxymethyl cellulose (CMC), styrene-butadiene rubber, polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl butyral, and a water-based acrylic resin.
[0093] In some embodiments, the weight percentage of the binder in the negative electrode material layer is 1.0% to 4.5%, such as 1.0%, 1.2%, 1.5%, 1.8%, 2.0%, 2.2%, 2.5%, 2.7%, 3.0%, 3.2%, 3.5%, 3.8%, 4.0%, 4.2%, 4.5%, or an interval formed by any two of the above values. In some embodiments, the negative electrode material layer in the negative electrode sheet includes a negative electrode material, a binder, and a conductive agent, and the weight percentage of the negative electrode material in the positive electrode material layer is 70% to 99%.
[0094] In some embodiments, the secondary battery further comprises a separator; Further preferably, the diaphragm includes at least one of a polypropylene diaphragm and a polyethylene diaphragm.
[0095] Further preferably, the diaphragm has a porosity of 40-60%.
[0096] Further preferably, an aramid coating is provided on the diaphragm.
[0097] By adopting the above-mentioned preferred porosity setting or the setting of the aramid coating, the interfacial reaction activity can be effectively reduced, and the transmission efficiency and safety performance of the overall secondary battery during the lithium ion transmission process can be improved.
[0098] The present invention is further described below with reference to specific examples, which are not to be construed as limiting the scope of the present invention. Example 1 A positive electrode sheet and a secondary battery, wherein the preparation method comprises the following steps: (1) Preparation of lithium nickel cobalt manganese oxide particles: nickel sulfate solution, cobalt sulfate solution and manganese sulfate solution are mixed according to the stoichiometric ratio, and then sodium hydroxide as a precipitant is added, and the pH is adjusted within the range of 12.1. The reaction temperature is kept at 55°C for 1 hour. After filtering, washing and drying, the obtained precursor is mixed with lithium carbonate in a molar ratio of lithium atoms to the total atoms of nickel, cobalt and manganese atoms in the precursor of 1.05:1 and ball milled. The mixture is heated to 800°C at 5°C / min under an oxygen atmosphere and calcined for 10 hours. The obtained material is crushed and sieved, mixed with the coating material, heated to 450°C at 5°C / min under an oxygen atmosphere and calcined for 4 hours. The mixture is sieved to obtain lithium nickel cobalt manganese oxide particles. (2) Preparation of positive electrode sheet: lithium nickel cobalt manganese oxide particles are used as positive electrode material, and then the positive electrode material, conductive agent acetylene black, conductive agent carbon nanotubes, and binder polyvinylidene fluoride are dispersed in N-methylpyrrolidone at a mass ratio of 98:0.5:0.5:1, and vacuum stirred to prepare a slurry, which is then coated on the current collector aluminum foil, and then dried, cold pressed, and striped, and then rolled, and then mechanically punched to provide concave holes to obtain the positive electrode sheet; the surface density of the positive electrode sheet is 249.5g / m 2 , compacted density is 3.35g / cm 3 ; (2) Preparation of negative electrode sheet: artificial graphite as negative electrode material, acetylene black as conductive agent, sodium carboxymethyl cellulose as thickener, and styrene-butadiene rubber as binder are dispersed in water in a mass ratio of 96.4:1:1.2:1.4, and vacuum stirred to prepare slurry, which is then coated on the current collector copper foil. After coating, drying, cold pressing, stripping, and rolling, the negative electrode sheet is obtained; the surface density of the negative electrode sheet is 172 g / m 2, compacted density is 1.66g / cm 3 ; (3) Preparation of electrolyte: EC, EMC and DEC were mixed in a volume ratio of 1:1:1 as a solvent. Then, lithium hexafluorophosphate and 2,2,2-trifluoroethyl methyl carbonate were added based on the total mass of the electrolyte to prepare an electrolyte with a lithium hexafluorophosphate concentration of 1 mol / L and a 2,2,2-trifluoroethyl methyl carbonate content of 1.8 wt%; (4) The positive electrode sheet, the commercially available PP separator, and the negative electrode sheet are stacked in order to form a battery cell, and the battery cell is placed in an outer packaging shell. After drying, the electrolyte is injected, and after vacuum packaging, standing, forming, and constant capacity, the lithium-ion secondary battery is obtained.
[0099] Examples 2 to 31, Comparative Examples 1 to 6 A positive electrode sheet and a lithium ion battery prepared therefrom, which differs from Example 1 only in the preparation process of the positive electrode sheet, wherein: The lithium nickel cobalt manganese oxide particles described in Example 13, Example 21, Example 26, Example 29, Comparative Example 4 and Comparative Example 6 were calcined once during preparation, and the resulting material was crushed and sieved before being mixed with a coating material, the coating material comprising 2000 ppm manganese dioxide and other coating materials, and the temperature was raised to 450°C at 5°C / min under an oxygen atmosphere, calcined for a second time for 4 hours, and sieved to obtain lithium nickel cobalt manganese oxide particles.
[0100] The parameters of each positive electrode sheet during preparation and the test results and parameters of the product are shown in Tables 1 and 2. The test methods of each product parameter are as described above. Taking a as an example, the a of the positive electrode sheet in Example 5 is pre-tested by DSC test, and the obtained Figure 1 The characteristic peak spectrum is then fitted and calculated to obtain S and T, and finally a is calculated. Wherein " / " indicates that the product of the embodiment / comparative example was not subjected to the process during preparation. For example, the positive electrode sheet in Example 2 was not punched, so there are no corresponding concave holes on the surface. The pore diameter, depth, and pore density of the concave holes in Table 1 are represented by " / ".
[0101] Table 1 Table 2 Effect Examples The lithium ion batteries obtained in each embodiment and comparative example were tested as follows: (1) Safety testing: (I) The secondary batteries obtained in each embodiment and comparative example were placed at 45° C. and allowed to stand for 24 h. Subsequently, they were fixed with a glass clamp at a pressure of 0.4 to 0.6 MPa and allowed to stand for 10 min. They were pre-charged at 0.02 C to a cut-off voltage of 3.2 V and allowed to stand for 10 min. Subsequently, they were charged at 0.05 C to a cut-off voltage of 3.4 V and allowed to stand for 10 min. Finally, they were charged at 0.08 C to a cut-off voltage of 3.75 V to complete formation. The formed secondary batteries were charged at a constant current rate of 0.33 C to the upper limit voltage, and then switched to constant voltage charging to a current of I ≤ 0.05 C. The battery core was wrapped with a heating wire and a thermocouple was attached. The battery core was then placed in an adiabatic reaction chamber. The ambient temperature was raised to the initial test temperature at a constant rate. Heating was stopped and the adiabatic mode was entered. The battery core temperature was allowed to equilibrate with the ambient temperature, and the battery core temperature change was continuously monitored. When the heat generation rate of the battery cell itself is detected to exceed the set threshold (0.02℃ / min), it is determined to be the self-heating starting temperature (T1); when the heat generation rate of the battery cell itself is detected to exceed the set threshold (1℃ / min), it is determined to be the starting point of thermal runaway (T2), and the T2 temperature is recorded.
[0102] (2) DCR test: The secondary battery was charged to 4.25 V at a constant current and constant voltage of 0.33 C at 25° C., with a cut-off current of 0.05 C; left for 10 min, discharged to 2.5 V at 0.33 C constant current, and this cycle was repeated for 2 cycles. The battery was then left for 10 min, charged to 4.25 V at 0.33 C constant current and constant voltage, discharged to 50% SOC of the second cycle discharge capacity, and left for 2 h. The initial voltage was recorded as V1, and the battery was discharged at a rate of 1 C for 18 s with a sampling interval of 0.1 s. After the discharge was completed, the voltage was recorded as V2, the 18S discharge current was I1, and DCR discharge (I1, 18s) = |V2-V1| / I1×1000.
[0103] The test results are shown in Table 3.
[0104] Table 3 According to Table 3, we can see that: (1) The secondary battery described in the present application coordinately regulates the heat release characteristic parameter a and the electrode tortuosity b of the ternary material in the positive electrode plate, so that the positive electrode plate satisfies the a / b range of 0.5 to 8. This not only effectively takes into account the improvement of the safety and stability of the electrode plate, but also improves the efficiency of the ternary material in lithium ion transmission, and has a low DCR. The thermal runaway starting temperature of the secondary battery is as high as 130°C or above, and the DCR can be controlled within 32mΩ, with excellent comprehensive performance. In contrast, the positive electrode plates of the secondary batteries described in the comparative examples do not take into account both the thermodynamic stability and kinetic performance of the positive electrode plates, and therefore cannot simultaneously achieve the safety and DCR test levels of the products of the embodiments.
[0105] (2) When the heat release characteristic parameter a and the tortuosity b of the positive electrode are adjusted synchronously, not only can the internal heat generation of the battery be controlled and the thermal stability and safety of the battery be adjusted, but also the wettability of the electrode and the electrolyte after contact can be high, the stress can be highly dispersed and uniform during charging and discharging, the electrochemical stability during lithium ion insertion and extraction can be excellent, and the kinetic performance can be better. According to the test results of each embodiment, when the ratio a / b of the two is further preferably within the range of 3 to 6, the electrochemical performance of the secondary battery is obviously better.
[0106] (3) On the other hand, when the exothermic characteristic parameter a of the electrode is further optimized in the range of 3 to 9, the interaction between the interface of the secondary battery positive electrode and the electrolyte is further reduced, and the internal heat generation is lower; when the tortuosity b of the electrode is further optimized in the range of 1.5 to 3.5, the ternary material not only avoids the negative impact caused by anisotropy, but also further improves its structural stability in the positive electrode, and the charge and discharge activity of the particles on the surface and bottom layers reaches a higher level, and the DCR value is lower. Therefore, when a and / or b of the secondary battery are further optimized, the electrochemical performance of the secondary battery will also be effectively improved.
[0107] (4) According to the comparison of various embodiments, after optimization, the initial temperature of thermal runaway of the secondary battery can reach above 160°C, and the DCR value can be further controlled at around 20mΩ.
Claims
1. A positive electrode plate, characterized in that: The positive electrode sheet includes a positive electrode material layer, the positive electrode material layer includes a positive electrode active material, and the positive electrode active material includes lithium nickel cobalt manganese oxide particles; The positive electrode sheet satisfies: a / b=0.5~8; Said a=S / T, wherein SJ / g is the total peak area of the exothermic characteristic peak of the positive electrode sheet between 190 and 290°C during the DSC test, and T°C is the temperature corresponding to the highest peak of the test exothermic characteristic peak; The b is the tortuosity of the positive electrode sheet.
2. The positive electrode sheet according to claim 1, wherein: The a / b=3~6.
3. The positive electrode sheet according to claim 1, wherein: The a=1.5~12.
4. The positive electrode sheet according to claim 1, wherein: The S=400~2600 J / g, and / or the T=190~290°C.
5. The positive electrode sheet according to claim 1, wherein: The b=1~5.
6. The positive electrode sheet according to claim 1, wherein: The lithium nickel cobalt manganate particles further include a shell, which includes at least one of Al2O3, ZrO2, LiAlO2, Li3PO4, lithium aluminum titanium phosphate, lithium lanthanum zirconium oxide, and lithium lanthanum titanate.
7. The positive electrode sheet according to claim 1, wherein: The particle size Dv50 of the positive electrode active material is 1.5-6 μm.
8. The positive electrode sheet according to claim 1, wherein: The positive electrode active material has a SPAN value of 1 to 1.
5.
9. The positive electrode sheet according to claim 1, wherein: The specific surface area of the positive electrode active material is 0.4 to 1.2 m 2 / g.
10. The positive electrode sheet according to claim 1, wherein: The porosity of the positive electrode sheet is 13-35%.
11. The positive electrode sheet according to claim 1, wherein: The compaction density of the positive electrode sheet is 3.25-3.65 g / cm 3 .
12. The positive electrode sheet according to claim 1, wherein: The structural formula of the lithium nickel cobalt manganese oxide is LiNi a Co b Mn c O2, where a is greater than 0 and less than 1; b is greater than 0 and less than 1; c is greater than 0 and less than 1; a+b+c=1.
13. The positive electrode sheet according to claim 1, wherein: A plurality of concave holes are provided on the positive electrode material layer, the ratio of the depth of the concave holes to the thickness of the positive electrode material layer is (0.2-0.96):1, and the pore diameter of the concave holes is 2-40 μm.
14. A secondary battery, characterized in that: Comprising the positive electrode sheet according to any one of claims 1 to 13.
15. The secondary battery according to claim 14, wherein: The secondary battery further includes a negative electrode plate, the negative electrode plate includes a negative electrode material layer, the negative electrode material layer includes a negative electrode active material, and the negative electrode active material includes at least one of graphite and silicon-based materials.
16. The secondary battery according to claim 15, wherein: The negative electrode active material includes graphite, and the positive electrode plate in the secondary battery satisfies b=1.8~5.
17. The secondary battery according to claim 15, wherein: The negative electrode active material includes a silicon-based material, and the positive electrode plate in the secondary battery satisfies b=1-4.
5.
18. The secondary battery according to claim 14, wherein: The secondary battery further includes an electrolyte, the electrolyte includes a solvent, and the solvent includes at least one of a carbonate solvent, a carboxylate solvent, an ether solvent, and a nitrile solvent.
19. The secondary battery according to claim 18, wherein: The carbonate solvent includes at least one of dimethyl carbonate, diethyl carbonate, ethylene carbonate, and ethyl methyl carbonate, and / or the carboxylate solvent includes at least one of ethyl acetate, ethyl propionate, and methyl acetate.
20. The secondary battery according to claim 18, wherein: The mass percentage of the carbonate solvent is 70-100% based on the mass of the total solvent in the electrolyte.
21. The secondary battery according to claim 18, wherein: The electrolyte further includes an additive, and the additive includes at least one of 2,2,2-trifluoroethyl methyl carbonate, pentafluoroethoxy cyclotriphosphazene, and vinyl sulfate.
22. The secondary battery according to claim 14, wherein: The secondary battery further includes a separator; the separator has a porosity of 40-60%, and / or the separator is provided with an aramid coating.
Citation Information
Patent Citations
Positive electrode active material, positive electrode plate and lithium ion secondary battery
CN112447964A
Positive electrode active material, positive electrode plate, lithium ion battery and application thereof
CN115995531A
Secondary battery and electric device
CN117174812A
Positive electrode active material, method for preparation thereof, positive electrode plate, lithium-ion secondary battery and related battery module, battery pack and apparatus
US20220185696A1
Cited By
Secondary battery
CN121484166A
A secondary battery
CN121484166B